Quinic acid derivatives and coumarin glycoside from the roots and stems of Erycibe obtusifolia. (December 2015) - Fan, Long; Wang, Ying; Liang, Ning; Huang, Xiao-Jun; Fan, Chun-Lin; Wu, Zhen-Long; He, Zhen-Dan; Li, Yao-Lan; Ye, Wen-Cai
Graphical abstract: Highlights: Two new compounds were isolated from the roots and stems of Erycibe obtusifolia . Structures were established on the basis of the spectroscopic methods. Quinic acid derivatives (1 –7 ) were screened for their in vitro anti-RSV activity. The dicaffeoylquinic acids (6 and7 ) displayed potent in vitro anti-RSV activity. Abstract: A new quinic acid derivative (1 ) and a new coumarin glycoside (8 ), together with six known compounds (2–7 ) were isolated from the roots and stems of Erycibe obtusifolia . The structures of the new compounds were elucidated by spectroscopic and chemical analyses. The in vitro antiviral activity against the respiratory syncytial virus (RSV) of seven quinic acid derivatives was evaluated by cytopathic effect (CPE) reduction assay. Among them, the dicaffeoylquinic acids (6 and7 ) displayed potent in vitro anti-RSV activity.